SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEB PADA TOKO BERKAH BERSAMA - YUSUF HARDJONO; NOVITA SETIANTI (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2023)
Abstract--- Problems with inventory are operational problems that are often faced by companies. If the amount of inventory is small and demand cannot be met, it can hamper the work process, as well as if the inventory is too large, this can result in losses to the company. Berkah Bersama is a store that in managing inventory data still uses a manual system by being recorded in a ledger. In addition to taking a long time, there is no specific information that informs about the amount of stock, so that when the stock runs out, the shop owner must know when the transaction process occurs.